2021
DOI: 10.3390/ijerph18041821
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Cardiometabolic Disease Risk for Indigenous Populations throughout the Lifespan

Abstract: Background: Indigenous people experience the greatest cardiometabolic disease disparity in the Unites States, yet high cardiometabolic disease risk factors do not fully explain the extent of the cardiometabolic disease disparity for Indigenous people. Stress, trauma, and racism occur at high rates within Indigenous communities and have not been well explored as significant contributors to cardiometabolic disease disparities despite emerging literature, and therefore will be described here. Methods: This descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 226 publications
(257 reference statements)
0
31
0
Order By: Relevance
“…The problem of poor health care associated with higher morbidity among the Indigenous populations is not limited to the inhabitants of the Sierra Nevada de Santa Marta. This can also be observed in other countries with regard to the number of communicable diseases [20][21][22][23][24], non-communicable diseases [25,26], or oral health [27]. Unfortunately, datasets on many indigenous people in other countries are incomplete or missing com-pletely.…”
Section: Discussionmentioning
confidence: 92%
“…The problem of poor health care associated with higher morbidity among the Indigenous populations is not limited to the inhabitants of the Sierra Nevada de Santa Marta. This can also be observed in other countries with regard to the number of communicable diseases [20][21][22][23][24], non-communicable diseases [25,26], or oral health [27]. Unfortunately, datasets on many indigenous people in other countries are incomplete or missing com-pletely.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of individual or combination of cardiometabolic risk factors has been termed 'cardiometabolic dysregulation' (CMD) or 'cardiometabolic risk' in the literature; a composite CMD score has been conveniently calculated as the simple count of cardiometabolic biomarkers in the respective high-risk ranges according to clinical criteria, which has the potential to be applied to different populations and would allow comparison across different studies. [31][32][33] Similar to AL, increased CMD was associated with stressful and traumatic life experiences, 34 cognitive decline, 32 and HRBs. 31 33 Shi et al 31 demonstrated that more healthy lifestyle behaviours, including abstinence from smoking, regular exercise, sufficient fruit and vegetable intake, less meat intake, modest alcohol intake and less television viewing time, were associated with reduced CMD among two generations of adults in the USA and Canada.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 84%
“…Others have adopted an historical lens to explain population-based health disparities: stress levels and adverse health outcomes among Black Americans cannot be understood without considering the history of enslavement (Dozier and Munn, 2020 ) and the afterlife of slavery (Davis, 2019 ); epidemics of communicable and non-communicable disease in South Africa cannot be understood without the history of colonial subjugation and apartheid (Coovadia et al, 2009 ), just as the history of Māori Indigenous people must be linked to the colonial history of New Zealand (Reid et al, 2019 ); disproportionate rates of diabetes in Indigenous populations cannot be understood without their shared experiences of colonization and expropriation of land (Fortier, 2008 ; Voaklander et al, 2020 ) and the brutal history of residential schools (Howard, 2014 ); and increased risk of cardiometabolic disease amongst Indigenous populations can also not be explained without considering the historical trauma of subjugation (Lewis et al, 2021 ). An expanded MSM model for Puerto Rican men adds to this literature and provides a theoretical underpinning and best-fit framework upon which to further strengthen and codify future intervention that gives weight to highlighting history and how this impacts the present.…”
Section: Discussionmentioning
confidence: 99%